Ethnicity, Migration, and Entrepreneurship in Indonesia - Cahyono, Erwin; Syafitri, Wildan; Susilo, Agus (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2021)
Extant studies demonstrate the vital roles of ethnicity group and culture influencing individual intention and decision to become an entrepreneur. Meanwhile, in the entrepreneurial decision, each ethnic group has different preferences regarding where to run it, at the origin or overseas. This study examines the roles of group ethnicity and culture in affecting the likelihood of an individual’s choosing entrepreneurship as their occupation using the combined data of the Indonesian Family Life Survey (IFLS) and the Population Census Report. Our findings substantiate that group ethnicity and culture significantly influence the likelihood of entrepreneurial decisions. Furthermore, using Javanese as a reference, we found the Balinese, Batak, Chinese, South Sumatran, and Minangkabau tend towards entrepreneurship. The difference is that the Balinese, Batak, Chinese, and South Sumatran tend to run their business around where they live, while the Minangkabau are overseas.